La estructura de la propiedad de la tierra en Murcia durante la conquista castellana - Antonio Vicente Frey Sánchez (Estudios de Historia de España, 2017)
Study about the structure of the soil’s property in the Murcia’s irrigated lands during the process of conquest and colonisation (XIII Century) from a register of Islamics owners made by the Royal Chancellery to confi rm the sell of an amount of possessions from the Order of St. John. So, from this and others studies about this time, I try to demonstrate the possibilities over prefeudal social structure in al-Andalus before the Castillian Conquest.